WHAT CAUSES INCOME INEQUALITY: ECONOMIC GROWTH OR FINANCIAL DEVELOPMENT? - Merter Akıncı; Gönül Yüce Akıncı; Ömer Yılmaz (Ankara Avrupa Çalışmaları Dergisi)
The paper investigates the linkage between growth, finance and inequality in the light of inverted-U hypothesis in the European Union member countries in theperiod 1995-2018. The findings of the multiple equations analysis indicate that economic growth and financial development act together, implying that growthboosts finance and vice versa. In addition, while the paper does not support the Kuznets hypothesis, the findings confirm the Greenwood-Jovanovic hypothesis,suggesting that the linkage between financial development and inequality is quadratic. That is to say, in the first phase of development, development of thefinancial markets is related to income inequality positively, however beyond the threshold level of finance, the linkage between finance and inequality becomesnegative.